Intravascular Hemolysis after Transcatheter Closure of a Huge Tubular Patent Ductus Arteriosus Using Cera-duct Occluder: Managed Successfully by Conservative Treatment (Journal of Armed Forces Medical College, Bangladesh, 2021)
Isolated patent ductus arteriosus (PDA) is seen in approximately 1 in 2000 full-term life birth neonate. Transcatheter device closure is widely considered as the treatment of choice for the patient diagnosed with PDA considering the safety, efficacy and less invasiveness. Residual flow following transcatheter device closure of PDA can result in haemolysis. Our patient was a case of 9.5 years old female child weighing13 kg diagnosed as a case of large tubular PDA with severe pulmonary hypertension by echocardiography. The patient had history of recurrent chest infection, breathlessness on exertion, and growth failure. The PDA was closed by transcatheter approach using Cera-duct occluder. The patient subsequently developed hemolysis which started 18 hrs after the intervention and the resolution of hemolysis achieved by conservative management within 72 hours.JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 90-92